The Influence of Motivation, Work Environment, and Work Discipline on Teacher Performance - Bedriani Yedesilva Hadiah; Fathorrahman; Asriana Kibtiyah (Journal of Educational Management Research, 2026)
Education is essential in developing high-quality, innovative, and adaptable human resources to meet the challenges of a changing world. The excellence of an educational institution is reflected in the effectiveness of its teaching and learning, which produces skilled and competitive students. Teacher performance plays a crucial role in this process, as teachers are directly involved in planning, implementing, and evaluating learning activities. Optimal teacher performance not only affects the quality of education but also contributes to achieving educational goals. This study examines the impact of work motivation, work discipline, and the work environment on teacher performance. A quantitative approach was used, with a questionnaire as the data collection instrument. The population consisted of 32 teachers, and a saturated sampling technique was applied, with 31 valid questionnaires. Data were analyzed using multiple linear regression with SPSS version 31. The results show that work motivation, work discipline, and the work environment significantly influence teacher performance. While work motivation had no significant individual effect, work discipline and the work environment did. Together, these three factors significantly improve teacher performance.